COMPARISON OF RECURRENCE OF ALLERGIC FUNGAL RHINOSINUSITIS AFTER ENDOSCOPIC SINUS SURGERY USING STEROIDS WITH OR WITHOUT ITRACONAZOLE (The Research of Medical Science Review, 2025)
Background:Allergic Fungal Rhinosinusitis (AFRS) is subtype of chronic rhinosinusitis characterized by hypersensitivity reaction to fungal elements, leading to persistent inflammation and a high recurrence rate after Endoscopic Sinus Surgery (ESS). Objective:to compare the recurrence rates, symptom improvement, and quality of life outcomes in AFRS patients receiving postoperative corticosteroids alone versus those receiving a combination of corticosteroids and itraconazole following ESS. Hypothesis: The addition of itraconazole to corticosteroid therapy will result in a statistically significant reduction in AFRS recurrence rates and improved symptom control compared to corticosteroids alone. Materials and Methods:A randomized clinical trial was conducted at Bahawal Victoria Hospital, Bahawalpur, from July 2023 to December 2024. Patients diagnosed with AFRS based on Bent and Kuhn criteria who underwent ESS were randomized into two groups: Group A (Corticosteroids Only) and Group B (Corticosteroids + Itraconazole). Primary outcomes included recurrence rates at 12 months post-surgery. Secondary outcomes assessed symptom improvement using SNOT-22 scores and quality of life using RSDI scores. Statistical analysis was performed using SPSS version 24.0. Results:Baseline characteristics were comparable between groups. The recurrence rate was significantly lower in Group B (10.0%) than in Group A (25.5%) (p = 0.004). Group B also demonstrated greater reductions in SNOT-22 (20 vs. 12 points, p< 0.001) and RSDI scores (25 vs. 15 points, p< 0.001), indicating better symptom relief and quality of life improvement. Conclusion:The addition of itraconazole to corticosteroid therapy significantly reduces AFRS recurrence rates and enhances post-surgical symptom relief and quality of life.